Transcriptomic Profiling Identifies Neutrophil-Specific Upregulation of Cystatin F as a Marker of Acute Inflammation in Humans - Sawyer, Andrew J.; Garand, Mathieu; Chaussabel, Damien; Feng, Carl G. (Frontiers in Immunology, 2021)
Cystatin F encoded by CST7 is a cysteine peptidase inhibitor known to be expressed in natural killer (NK) and CD8+ T cells during steady-state conditions. However, little is known about its expression during inflammatory disease states in humans. By exploring several cohorts of public transcriptome data comprising 44 individual datasets, we showed that CST7 is upregulated in the blood during a diverse set of infectious and non-infectious inflammatory conditions. Interestingly, this upregulation of CST7 was neutrophil-specific, while its expression was unchanged in NK and CD8+ T cells during sepsis. Further analysis showed that known microbial products or cytokines commonly associated with inflammation failed to upregulate CST7 expression, suggesting that its expression in neutrophils is induced by an endogenous serum factor commonly present in human inflammatory diseases. Overall, through the identification of CST7 upregulation as a marker of acute inflammation in humans, our study demonstrates the value of publicly available transcriptome data in knowledge generation and potential biomarker discovery.